Poetry Writing Skills for Grade IV SDIT ALIF Students Using the Acrostic Technique - Ika Wijayanti (Mitra Palupi, 2023)
Background: The ability to write is a human effort to express thoughts and emotions contained in written language. Writing poetry is a productive activity and the ability to write poetry can be achieved through systematic teaching and intensive training. Learning poetry provides many benefits for students. Students can express themselves and expand their vocabulary. In addition, students know how to use language to understand, develop, and convey ideas and information to readers. Purpose: The purpose of this study was to determine the poetry writing skills of fourth-grade students at SDIT ALIF after using the acrostic technique. Design and methods: This research was compiled using a descriptive method based on analysis guidelines through a qualitative approach. Qualitative descriptive is the term used in qualitative research for descriptive research. The researcher's analysis technique uses observation and document analysis. Results: This study shows that the results of the analysis of the poetry writing skills of fourth grade students at SDIT ALIF with the acrostic technique are students who match the skills of writing acrostic poetry by 75%. Students who do not fit the skills of writing acrostic poetry 25%. Conclusion (1) From the results of the analysis of the Poetry Writing Skills of Grade IV Students at SDIT ALIF using the acrostic technique, it was found that 75% of the 61 samples fit the skills of writing acrostic poetry. In the activity of writing poetry, class IV SDIT ALIF students using the acrostic technique carried out quite well, but there were some students who were still lacking in writing acrostic poetry, such as the discrepancy between the word patterns written vertically and the suitability of the content. and title and unable to express ideas. his thoughts into poetry. (2) This research was said to be quite successful because 75% of the 60 samples of poetry written by children were able to express their ideas, experiences, thoughts, expressions, and imagination into well-structured writing so as to give a good impression. readers' ideas about the meaning or message of the posts that have been written